2013
DOI: 10.1186/1916-0216-42-46
|View full text |Cite
|
Sign up to set email alerts
|

Osteoradionecrosis of the mandible: A case series at a single institution

Abstract: BackgroundOsteoradionecrosis (ORN) defines exposed irradiated bone, which fails to heal over a period of 3–6 months without evidence of residual or recurrent tumor. In the previous decades, a staging and treatment protocol suggested by Marx, has dominated the approach to ORN. However, recently this paradigm is shifting. The purpose of this study was to evaluate our institutional experience in managing ORN through a retrospective review of case series from a large urban academic cancer centre.MethodsA retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
5
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 15 publications
6
40
5
4
Order By: Relevance
“…The majority of studies dealing with ORN have focused on risk factors associated with the causation of ORN (Morrish et al, 1981, Kluth et al, 1988, Jereczek-Fossa and Orecchia, 2002, Reuther et al, 2003, Gomez et al, 2011, Niewald et al, 2013, Tsai et al, 2013. To our knowledge, only four studies were found dealing with the severity of ORN (Store and Boysen, 2000, Notani , Chopra et al, 2011, Gevorgyan et al, 2013. They either consisted of a small sample size (Gevorgyan et al, 2013) or focused on the severity of ORN proposing new classification systems or modalities of therapy (Store andBoysen, 2000, Notani et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies dealing with ORN have focused on risk factors associated with the causation of ORN (Morrish et al, 1981, Kluth et al, 1988, Jereczek-Fossa and Orecchia, 2002, Reuther et al, 2003, Gomez et al, 2011, Niewald et al, 2013, Tsai et al, 2013. To our knowledge, only four studies were found dealing with the severity of ORN (Store and Boysen, 2000, Notani , Chopra et al, 2011, Gevorgyan et al, 2013. They either consisted of a small sample size (Gevorgyan et al, 2013) or focused on the severity of ORN proposing new classification systems or modalities of therapy (Store andBoysen, 2000, Notani et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…5,14,16 Em relação aos cuidados locais, nenhum dos artigos selecionados especificou como esses cuidados foram realizados. Na literatura essa abordagem é diversa, com utilização de digluconato de clorexidina e iodopovidona para limpeza das feridas.…”
Section: Discussionunclassified
“…[6,7] Diseased tooth extractions (odontogenic and periodontal disease), denture trauma after irradiation, [8] abuse of alcohol and tobacco are also considered as risk factors for ORN. [6,9] Other factors associated with ORN are location of primary tumor in tongue, floor of mouth, alveolar ridge, reteromolar trigone, tonsil, stage III/IV cancer, doses above 60Gy of radiation, poor nutritional status which could affect wound healing. Prevention of ORN is an extremely important part of the comprehensive management of patients who undergo external beam radiation therapy to the head and neck.…”
Section: Discussionmentioning
confidence: 99%